2010
DOI: 10.1111/j.1526-4637.2010.00867.x
|View full text |Cite
|
Sign up to set email alerts
|

A Risk-Benefit Assessment of Paracetamol (Acetaminophen) Combined with Caffeine

Abstract: Paracetamol/caffeine (1,000 mg/130 mg) is effective and safe for use in acute management of pain. The hepatotoxicity of overdoses of paracetamol results from its oxidative metabolism, caffeine does not produce any increase in oxidative metabolism of therapeutic concentrations of paracetamol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…It was found that CAF slightly enhances the inhibitory effects of APAP on genes involved in pain perception and modulation ( Figure 7). These results may explain the observed increase in the clinical efficacy of APAP at the cellular scale induced by co‐administration of CAF 8, 9, 10…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…It was found that CAF slightly enhances the inhibitory effects of APAP on genes involved in pain perception and modulation ( Figure 7). These results may explain the observed increase in the clinical efficacy of APAP at the cellular scale induced by co‐administration of CAF 8, 9, 10…”
Section: Discussionmentioning
confidence: 90%
“…A mean toxic dose of APAP (34 g) was identified in literature at a sublethal level,32, 33 whereas the dose level of CAF (4.4 g) was derived from a relative dose ratio of 1000:130, according to therapeutic indications used in drug combination therapy 8, 9, 10. Note that APAP and CAF are frequently co‐administered because CAF is supposed to enhance the analgesic effect of APAP 8, 9, 10…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations